Religious Buildings Made in Byzantium Old Monuments, New Interpretations - Jevtić, Ivana; Kontogiannis, Nikos D.; Stanković, Nebojša (New Approaches to Byzantine History and Culture, 2024)
XXIII, 417 p. 74 illus.